2019
DOI: 10.1002/pbc.27930
|View full text |Cite
|
Sign up to set email alerts
|

Optimal neoadjuvant chemotherapy duration in Wilms tumour with intravascular thrombus: A literature review and evidence from SIOP WT 2001 trial

Abstract: Introduction:Preoperative chemotherapy is recommended for children with Wilms tumour with intravascular extension. Extended chemotherapy may improve resectability, but increase tumour adherence to vascular endothelium, precluding complete resection. To evaluate the optimal length of preoperative treatment, we report a two-part review comprising systematic review of the literature and investigation of patients treated in the International Society of Paediatric Oncology (SIOP) WT 2001 trial. Methods: Studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
2
25
0
2
Order By: Relevance
“…A previous meta-analysis found no survival benefits to extended courses of chemotherapy in Wilms patients with intravascular extension, confirmed by the present study 27 . These longer courses of chemotherapy may reflect the lack of radiological regression of thrombus, indicating the absence of macro- or microscopic response, although a single study reported no association between macroscopic appearances and microscopic response 25 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A previous meta-analysis found no survival benefits to extended courses of chemotherapy in Wilms patients with intravascular extension, confirmed by the present study 27 . These longer courses of chemotherapy may reflect the lack of radiological regression of thrombus, indicating the absence of macro- or microscopic response, although a single study reported no association between macroscopic appearances and microscopic response 25 .…”
Section: Discussionsupporting
confidence: 90%
“…Logistic regression was used to analyse the relationship between thrombus viability and duration of chemotherapy, using data from individual patients where complete and amenable to comparison. Patients were then categorized by the duration of neoadjuvant chemotherapy as: short course, less than 4 weeks; standard course, 4–6 weeks; or extended course, more than 6 weeks 27 . Where the duration of neoadjuvant chemotherapy was reported in terms of cycles, courses, doses or protocols, standardized Wilms tumour regimens for the same agents were used to convert these terms to weeks, for adequate comparisons to be made.…”
Section: Methodsmentioning
confidence: 99%
“…Extending neoadjuvant therapy beyond 6 weeks is not associated with improved surgical resection, further thrombus regression, or survival advantage. 53 The panel recommends neoadjuvant chemotherapy for 6 to 12 weeks for patients with bilateral WT requiring nephron-sparing resection. (Strong recommendation; Quality of evidence: Very Low) Panel deliberation.…”
Section: Operative Phasementioning
confidence: 99%
“…Следует отметить, что несмотря на то, что наличие опухолевого тромбоза НПВ общепризнанно рассматривается как показание к проведению неоадъювантной химиотерапии, вопрос о ее длительности и количестве используемых препаратов остается открытым [26]. L. Morris и соавт.…”
Section: обсуждение и обзор литературыunclassified
“…Интересными в контексте описываемого случая явились данные о том, что гистологический тип опухоли влиял на частоту регресса опухолевого тромба, при этом сокращение размеров тромба у пациентов со стромальным вариантом нефробластомы было выявлено лишь в 17% случаев. В связи с этим в протоколе SIOP-RTSG 2016 при наличии опухолевого тромбоза НПВ у пациентов с локализованными формами нефробластомы рекомендовано проведение стандартной предоперационной химиотерапии по схеме AV в течение 4 нед [26].…”
Section: обсуждение и обзор литературыunclassified